The Role of Ca2+/PI3K/Akt/eNOS/NO Pathway in Astragaloside IV-Induced Inhibition of Endothelial Inflammation Triggered by Angiotensin II - Shiyu Zhang; Shijie Li; Shiyang Xie; Lin Cui; Yuan Gao; Youping Wang (Hindawi Limited, 2024)
Inflammation induced by angiotensin II (Ang II) is a key event in the progression of numerous cardiovascular diseases. Astragaloside IV (AS-IV), a glycoside extracted from Astragalus membranaceus Bunge, has been shown to inhibit Ang II-induced inflammatory responses in vivo. However, the mechanisms underlying the beneficial effects are still unclear. This study investigated whether AS-IV attenuates endothelial inflammation induced by Ang II via the activation of endothelial nitric oxide synthase (eNOS)/nitric oxide (NO) pathway. Human umbilical vein endothelial cells (HUVECs) were cultured in the presence of AS-IV with or without the specific inhibitor of NOS or Ca2+- and phosphatidylinositol 3-kinase (PI3K)/Akt-dependent cascade prior to Ang II exposure. Incubation of HUVECs with AS-IV enhanced NO production and eNOSser1177 phosphorylation. These responses were abrogated by the inhibition of NOS or Ca2+- and PI3K/Akt-dependent pathway. In addition, preincubation of HUVECs with AS-IV inhibited Ang II-induced cytokine and chemokine production, adhesion molecule expression, monocyte adhesion, and nuclear factor kappa B (NF-κB) activation as evidenced by the attenuation of inhibitor of kappa B alpha phosphorylation and subsequent NF-κB DNA binding. These effects of AS-IV were abolished by the suppression of NOS or Ca2+- and PI3K/Akt-dependent cascade. Our findings indicate that AS-IV attenuates inflammatory responses triggered by Ang II possibly via the activation of Ca2+/PI3K/Akt/eNOS/NO pathway in endothelial cells.